2003
DOI: 10.1023/a:1025659822427
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: The purpose of this study is to discern what factors affect the longevity of amalgam and of composite restorations by dentists who perform posterior restorations. Data are obtained from the Washington Dental Service and contain 1.5 million patient encounters representing visits to 23,000 providers from January 1993 through 31 December 1999. Analysis of provider performance is estimated through Data Envelopment Analysis. The principal finding is that the most efficient dentists produce posterior restorations th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…It could be that these clinicians are more efficient. (25) The very busy and the not busy practices had restorations with higher survival rates. The explanation may be related to a complex conundrum of practice style, work environment, and clinical approach.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It could be that these clinicians are more efficient. (25) The very busy and the not busy practices had restorations with higher survival rates. The explanation may be related to a complex conundrum of practice style, work environment, and clinical approach.…”
Section: Discussionmentioning
confidence: 99%
“…One study found that more-efficient operators had higher restoration survival rates. (25) Clinicians’ age and educational background may impact restoration longevity,(26) as well as the type of restorative material selected. One study showed that female dentists were more likely to place amalgam restorations than males.…”
Section: Introductionmentioning
confidence: 99%
“…The process is also useful for moderately soluble drugs when a high concentration of drug in a low volume of fluid is desired. 3) Many different techniques can be used to prepare nanocrystal formulations of a drug powder such as, homogenization, [4][5][6][7][8][9][10][11][12] co-precipitation, spray drying, 9,13) milling, [4][5][6][7][8]14) and precipitation. Nanocrystal dispersions comprise water, active drug substances and a stabilizer.…”
mentioning
confidence: 99%